EFFICACY OF COMBINATION OF SYSTEMIC AND NON-SYSTEMIC FUNGICIDES AGAINST STEM ROT OF RICE - NISHANT PRAKASH,; SMITA PURI, (The Bioscan, 2012)
Stem rot of rice, caused by Sclerotia oryzae is a serious threat to rice production in North India. Fungicides only provide limited control of this pathogen but also have ill effects on the environment. In an attempt to develop better integrated strategies for management of this disease, in vitro experiments were conducted to find out the compatibility of different systemic and non systemic fungicides with Sclerotia oryzae and fungal and bacterial biocontrol agents. Among the five systemic fungicides tested, Contaf was highly effective in reducing mycelial growth of S. oryzae at low concentration. Of the four non-systemic (contact) fungicides Chlorothalonil was highly effective against the pathogen in vitro. Trichoderma and Pseudomonas isolates showed variable responses against the tested fungicides in vitro. The results indicated that Bavistin was comparatively less inhibitory to the bioagents and it also gave satisfactory inhibition to the pathogen growth. So the combination of Bavistin at low concentration with bioagents increased the efficacy of both, subsequently reducing the chances of development of resistant pathogenic strains. More detailed studies are required to elucidate formulations of antagonists and alternative fungicides for more successful protection against the disease.